Alternative Dispute Resolution in the Context of Customary Law Issues in Indonesia - Ahmad Muliadi; Yuliasara Isnaeni (Universitas Islam Sultan Agung, 2026)
The Baduy community is well known for its strong adherence to customary law, which governs all aspects of life, including dispute resolution. The process is typically carried out through deliberation that prioritizes peace (silih hampura) and is led by customary leaders such as the Pu’un and Jaro. This study aims to examine alternative mechanisms for resolving customary law disputes among the Baduy people in Lebak Regency, Banten Province, with a focus on the forms of alternative dispute resolution and the challenges faced in the modern era. The research employs normative juridical and empirical juridical methods, with the study conducted in Lebak Regencys. Data were obtained through literature studies and interviews with customary leaders and members of the Baduy community. The results indicate that dispute resolution within Baduy customary law is restorative in nature, emphasizing the restoration of social relations over punitive measures. However, various challenges affect the effectiveness of this dispute resolution system, including the limited jurisdiction of customary law that does not extend to external parties, lack of understanding of customary law among state officials, the erosion of adherence among the younger generation due to modernization, suboptimal legal protection from the state, and the limited capacity of customary institutions themselves. If customary efforts fail to resolve disputes, cases are then handed over to national law as an ultimum remedium. This study recommends strengthening the synergy between customary law and national law through practical formal recognition, enhancing the capacity of customary institutions, and fostering intergenerational education to ensure the sustainability of customary-based dispute resolution while maintaining legitimacy within the framework of national law.